FAK inhibition alone or in combination with adjuvant therapies reduces cancer stem cell activity - Simon Timbrell (Nature Portfolio, 2021)
Abstract Cancer stem-like cells (CSC) contribute to therapy resistance and recurrence. Focal adhesion kinase (FAK) has a role in CSC regulation. We determined the effect of FAK inhibition on breast CSC activity alone and in combination with adjuvant therapies. FAK inhibition reduced CSC activity and self-renewal across all molecular subtypes in primary human breast cancer samples. Combined FAK and paclitaxel reduced self-renewal in triple negative cell lines. An invasive breast cancer cohort confirmed high FAK expression correlated with increased risk of recurrence and reduced survival. Co-expression of FAK and CSC markers was associated with the poorest prognosis, identifying a high-risk patient population. Combined FAK and paclitaxel treatment reduced tumour size, Ki67, ex-vivo mammospheres and ALDH+ expression in two triple negative patient derived Xenograft (PDX) models. Combined treatment reduced tumour initiation in a limiting dilution re-implantation PDX model. Combined FAK inhibition with adjuvant therapy has the potential to improve breast cancer survival.